2017
DOI: 10.1080/13625187.2017.1412427
|View full text |Cite
|
Sign up to set email alerts
|

Perforation risk and intra-uterine devices: results of the EURAS-IUD 5-year extension study

Abstract: The incidence of uterine perforations in this study was low, although higher than the commonly reported rate. Approximately one third of perforations are detected 12 months after insertion. Clinical sequalae of perforations are generally mild and associated with a very low risk of injury to intra-abdominal and pelvic structures. Implications Uterine perforation is a rare risk associated with intra-uterine device use. Late diagnosed perforations can occur, although women can be reassured that the morbidity asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 11 publications
1
42
0
6
Order By: Relevance
“…However, a 5-year follow-up research carried out in Europe by Barnet et al found that patients diagnosed with perforation after 12 months of IUD insertion had less probabilities of presenting symptoms. Additionally, the same research revealed that the main symptoms were bleeding and pain (3). In this case, our patient was asymptomatic for two years; she eventually attended consultation for pelvic pain and dysmenorrhea and the transvaginal ultrasound showed a fragmented and intramyometrial IUD, thus, we decided to perform a hysteroscopy to retrieve the device.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, a 5-year follow-up research carried out in Europe by Barnet et al found that patients diagnosed with perforation after 12 months of IUD insertion had less probabilities of presenting symptoms. Additionally, the same research revealed that the main symptoms were bleeding and pain (3). In this case, our patient was asymptomatic for two years; she eventually attended consultation for pelvic pain and dysmenorrhea and the transvaginal ultrasound showed a fragmented and intramyometrial IUD, thus, we decided to perform a hysteroscopy to retrieve the device.…”
Section: Discussionmentioning
confidence: 78%
“…However, its success rate varies between 44% and 100%, depending on the presented complication and the surgeon's expertise. Up to 25% may have the necessity of conversion to laparotomy (3,6,8).…”
Section: Discussionmentioning
confidence: 99%
“…The intrauterine device is a safe contraceptive method, with a 99% of effectiveness and widely used worldwide [4 Nonetheless, one of its more serious complications is the uterine perforation that occurs with an incidence of 1.6 to 2.1 per 1000 insertions [3]. Perforations are reported to be mostly located in the myometrium and the greater omentum, with a frequency of 21%.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain their safety and optimal effect, replacement is recommended after 5 to 10 years, depending on the type of IUD. Despite their durability and effectiveness, their use is not without complications, in some cases requiring extraction …”
mentioning
confidence: 99%
“…Despite their durability and effectiveness, their use is not without complications, in some cases requiring extraction. [2][3][4] In nonpregnant women, extraction of an IUD is usually a simple procedure. Under direct view with a vaginal speculum, smooth and progressive traction of the strings is performed until complete retrieval of the IUD from the uterine cavity.…”
mentioning
confidence: 99%